Brief notes on transmission of shares in case of death of shareholder in private limited companies - Silva, Stefanie Esteves; Machado, Maria João (Revista Jurídica Portucalense, 2019)
In case of death of a partner of a private limited company, the transfer of it’s share will take place, in principle, under the general terms of the law of succession. However, there are exceptions that escape the natural succession phenomenon regulated by the law of succession, if, for example, contrary stipulation is provided for in the social contract. The social contract may contain clauses restricting the transmission of social participation to its successors, in so far as it establishes conditions of non-transferability of the share to the successors of the deceased partner, and in such cases it must be amortized (article 232 and seq. of the Commercial Companies Code) or acquired by the company (article 220 of the CCC), by partners or by third parties. The surviving members have 90 days to decide on one of the measures, otherwise the share will be definitively passed on to the heirs (article 225 nº 2 of the CCC). The social contract may also place the transfer of the share in the dependency of the successors of the deceased shareholder and mention, in general terms, the possibility of the transfer being in some way conditioned to the will of the shareholders successors. As such, they must declare it in writing to the company within 90 days of the death (article 226 of the CCC).